When is investor-state dispute settlement appropriate to resolve investment disputes? An idea for a rule-of-law ratings mechanism - John P. Gaffney (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
This Perspective considers the idea of a rule-of-law ratings mechanism by a designated agency, rating the degree of respect for the rule of law by domestic courts in a given country or region, in order to determine whether investor-state disputes should be resolved by national courts or investor-state dispute settlement.
Keywords: 330